Results of studying the Cu/ITO transparent back contacts for solar cells SnO2:F/CdS/CdTe/Cu/ITO - Deyneko, Natalya; Semkiv, Oleg; Soshinsky, Olexander; Streletc, Victor; Shevchenko, Roman (Eastern-European Journal of Enterprise Technologies, 2018)
We have studied transparent rear contacts Cu/ITO for the CdTe-based solar cells intended to be used in tandem and two-side sensitive instrumental structures. Creating an ohmic contact to the base layers of p-CdTe under industrial production is not practical as only platinum has the work function of electrons required for forming the ohmic transition. That is why the tunnel contacts are typically formed, using the thin films containing copper or copper chalcogenides. However, the diffusion of copper into the base layer leads to the degradation of initial parameters of film solar cells based on CdS/CdTe. Therefore, conditions for creating the transparent rear contacts when using a layer of copper require examination. It was established that the preliminary application of a nanodimensional layer of copper on the CdTe surface in order to form a rear electrode allows the formation of a quality tunneling contact. It is shown that the obtained instrumental structures demonstrate high degradation resistance. After 8 years of operation, the magnitude of efficiency for the examined PEC is nearly identical to the initial value. Studying the light volt-ampere characteristics of the SnO2:F/CdS/CdTe/Cu/ITO solar cells when illuminated from both sides allowed us to establish significant differences between the initial parameters and the light diode characteristics at illumination from a glass substrate and from the rear transparent electrode. The established differences are due to the influence of a rear diode on the efficiency of photovoltaic processes in the base layer. The examined structure implements an inverse diode regime when a rear contact represents a diode, connected in series relative to the principal diode, which leads to the lower values of efficiency at illumination from the rear electrode. The results obtained demonstrate the need to reduce the thickness of the base layer in order to create effective two-side sensitive elements.